Indian Twin Deficits: The Role of Inflation and Money Supply - Bedarkar, Madhura; Gopalkrishnan, Santosh; Khairnar, Kunal (Indian Journal of Finance, 2016)
The study explored the role of inflation and money supply in the twin deficits hypothesis using the IS-LM framework and posited that inflation could be the mediating variable which explains why a higher fiscal deficit may lead to worsening of the current account balance. This may hamper the effectiveness of the monetary policy and long run output growth. We tested the model empirically on Indian data using Johansen's cointegration test to find evidence that fiscal deficit, current account deficit, inflation, and money supply have a long-run relationship.